Diagnostic uncertainty during the transition to secondary progressive multiple sclerosis. (October 2014) - Sand, Ilana Katz; Krieger, Stephen; Farrell, Colleen; Miller, Aaron E
Secondary progressive multiple sclerosis (MS) is typically defined as deterioration independent of relapses for ≥ 6 months following an initial relapsing–remitting course; however, this definition is not always easily applied in clinical practice and the declaration of the change in clinical phenotype is often delayed. To identify the length of time required to re-classify relapsing–remitting MS (RRMS) patients whom have clinically transitioned to secondary progressive MS (SPMS) in clinical practice. We reviewed 123 patients with long-term follow-up and identified a sub-group whom transitioned from RRMS to SPMS, then characterized this transition period. There were 14/20 patients who transitioned during the follow-up period that had visits with uncertainty related to the clinical phenotype characterized by possible, but not definitive progression. The mean duration of this period of uncertainty was 2.9 ± 0.8 years. A period of diagnostic uncertainty regarding the transition from RRMS to SPMS existed in many of our patients. Potential reasons included the subtle nature of early progressive disease and caution in applying a progressive label, in light of the lack of evidence-based treatments as well as third-party payer concerns. Delay in definitive identification of an SPMS phenotype has a variety of implications related to patient care and research.